A novel molybdenum oxide–Starbon catalyst for wastewater remediation. Issue 29 (16th July 2020) - Kaur, Jaspreet; Kaur, Khushwinder; Mehta, Surinder K.; Matharu, Avtar S.
Abstract : A highly efficient molybdenum–Starbon composite for catalytic reduction of 4-nitrophenol to 4-aminophenol for potential application in wastewater treatment. Abstract : The exploration of novel media for environmental remediation, in particular wastewater treatment, is a global imperative. Herein, the in situ green synthesis, characterisation and application of a novel Starbon™ composite comprising molybdenum oxide nanoparticles are reported. Starbons™ are carbonaceous mesoporous materials derived from starch with applications ranging from chromatography to gas capture. The molybdenum (Mo) loading, evidenced by inductively coupled plasma-mass spectrometry (ICP-MS), was 179.337 mg g −1, and the molybdenum oxide nanoparticles were observed via transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy (EDX). The Mo-containing composite was an efficient catalyst for the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) in the presence of sodium borohydride, NaBH4 ( k = 11.2 × 10 −2 min −1 ). The Mo-composite showed superior 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical quenching activity with a low inhibitory concentration [IC50 = 1.006 mg ml −1 ] and ferric reducing power compared with other green synthesised composites and nanoparticles. The novel Mo-containing Starbon™ composite has real time applications in water treatment such as in catalysis, adsorption and filtration.